{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Lecture+11+Notes (2)

# Lecture+11+Notes (2) - 1 14:440:127 Introduction to...

This preview shows pages 1–3. Sign up to view the full content.

1 14:440:127– Introduction to Computers for Engineers Notes for Lecture 11 Rutgers University, Fall 2010 Instructor- Brenda V. Cortez 1 Recursion There’s a very interesting technique in computer programming called recursion , in which you write a function that calls a variation of itself to get the answer . Eventually, this string of functions call- ing itself stops at some base case , and the answers work their way back up. Of course, in order to understand recursion, you must understand recursion. (haha! Get it?! Recursive Joke!). As a first example, let’s consider calculating a factorial. If you want to calculate n! ( n facto- rial), you could write this as n! = n * (n 1)! . In other words, “n factorial” is actually just n times “n-1 factorial” . Thus, we’ve defined the factorial of n using factorial again. In other words, “to calculate the factorial (of n ), calculate the factorial (of n-1 ).” Eventually, you need to get down to a base case. What should your base case be? Well, 1! is 1 , so make that your base case. So how do you write this as Matlab code? Often, you’ll include the base cases first . function y = myfactorial(x) if(x==1) y = 1; else y = x * myfactorial(x-1); end function y = myfactorial(x) y = 1; for z = x:-1:1 y = y*z; end Why do we use recursion? Well, it’s sometimes very simple to define a problem recursively, particu- larly when creating distributed algorithms in networks , or performing searches, or that sort of thing. Pretty much all of the problems we’re showing you in lecture can be done about as easily with iterative (performing something over and over again) algorithms using loops, but not all algorithms can easily be written iteratively. Let’s now look at how you can use recursion to calculate a term in the Fibonacci sequence. Recall that the first two terms of the Fibonacci sequence are 1, and all other terms are the sum of the previous two terms. We’ll make F(1) = 1 and F(2) = 1 our base cases. Those are the cases where we trivially know the answer!

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
2 If you wanted to find the fifth term of the Fibonacci sequence, F(5) , you could say that: F(5) = F(4) + F(3). So now, we need to know what F(4) and F(3) are. F(4) = F(3) + F(2). So now, we need to know what F(3) is. F(2) is 1, by the base case. F(3) = F(2) + F(1). Nice, F(2) = 1, and F(1) = 1, by our base cases. Thus, we work backwards: F(3) = F(2) + F(1) = 1 + 1 = 2. F(4) = F(3) + F(2) = 2 + 1 = 3. F(5) = F(4) + F(3) = 3 + 2 = 5. In English, we’ve essentially said that the “nth fibonacci number is the ( n-1 )st fibonacci num- ber plus the ( n-2 )nd fibonacci number.” Again, we’ve defined a fibonacci number in terms of... well, other fibonacci numbers. We keep calling our Fibonacci number function for smaller and smaller numbers until we got to the base cases. We define our base cases as the first and second fibonacci number - they’re both 1 , which we know pretty trivially. Then, we worked backwards, filling in the blanks. So how do you write this as Matlab code? Again, include the base cases first.
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}